Rare brain and pulmonary abscesses caused by oral pathogens started with acute gastroenteritis diagnosed by metagenome next-generation sequencing: A case report and literature review - Chen, Minhua; Lai, Zhiyi; Cheng, Mingjun; Liang, Tianyu; Lin, Zongbin (Frontiers in Cellular and Infection Microbiology, 2022)
Odontogenic brain and pulmonary abscesses are extremely rare infectious diseases. It is mainly caused by the upward or downward transmission of local infection or blood-borne spread. In recent years, with the wide application of some novel testing methods in clinical practice, the diagnosis of unexplained infections such as odontogenic abscesses in different organs has gradually become clear. We report a case of a 21-year-old male who was healthy and had not received any oral treatment before onset. He started with acute gastroenteritis-related symptoms, then developed meningitis-related symptoms seven days later with septic shock. No obvious abscess lesions were found on head computed tomography (CT) at admission, and the etiology was not clear by routine examination, which was very easy to misdiagnose as a serious infection caused by intestinal pathogens. But odontogenic pathogens were found both in his blood and cerebrospinal fluid through metagenomic next-generation sequencing (mNGS) analysis. Subsequently, rechecked imaging examination displayed multiple brain and pulmonary abscesses. Finally, it was diagnosed as an odontogenic brain and pulmonary abscess. After an extremely lengthy anti-infection course (13 weeks of intravenous antibiotics plus 2 weeks of oral antibiotics) and surgery, the patient was improved and discharged from the hospital. From this case, we could see that the development of new diagnostic technologies such as mNGS plays an important role in the early and confirmed diagnosis of diseases previously difficult to diagnose such as odontogenic polymicrobial infections and ultimately helps to improve the prognosis of these patients.